Development and validation of spectrophotometric methods for simultaneous determination of sitagliptin and simvastatin in binary mixture - Abdel-Gawad, Sherif Abdel-Naby; Elsherif, Zeinab Abdelaziz (European Journal of Chemistry, 2012)
Simple, selective and precise spectrophotometric methods were adopted for simultaneous determination of sitagliptin (SIT) and simvastatin (SIM) in new co-formulated pharmaceutical dosage form. In the first method, SIT was determined by measuring its zero order absorbance at 266.4 nm in the range of 40-360 µg/mL in the presence of up to 70% of SIM. While, the two cited drugs were determined simultaneously using third derivative method by measuring the sum of peak amplitudes (peak & valley) at 275.3-280.3 nm and 240.5-244.7 nm in the ranges of 40-360 µg/mL and 2-18 µg/mL for SIT and SIM, respectively. In the second method, the first derivative of ratio spectra method was applied by measuring the peak height at 255.9 and 275.2 nm using 18 µg/mL SIM as devisor over a concentration range of 40-360 µg/mL of SIT and at 228.3, 240.5 and 248 nm using 100 µg/mL of SIT as divisor over a concentration range 2-18 µg/mL SIM. In the third method the ratio subtraction spectrophotometric method was used, where SIM can be determined by dividing the spectra of the mixtures by the spectrum of SIT (40 µg/mL) followed by subtracting the constant absorbance value of the plateau, then finally multiply the produced spectrum by the spectrum of the devisor. Laboratory prepared mixtures were successfully tried for the three compositions of tablets (10, 20 and 40 mg of SIM) with 100 mg of SIT. The developed methods were validated as per International Conference of Harmonization guidelines.